2020
DOI: 10.1007/s11606-020-06276-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Electronic Health Record “Nudge” on Opioid Prescribing and Electronic Health Record Keystrokes in Ambulatory Care

Abstract: Background Multiple policy initiatives encourage more cautious prescribing of opioids in light of their risks. Electronic health record (EHR) redesign can influence prescriber choices, but some redesigns add to workload. Objective To estimate the effect of an EHR prescribing redesign on both opioid prescribing choices and keystrokes. Design Quality improvement quasi-experiment, analyzed as interrupted time series. Participants Adult patients of an academic multispecialty practice and a federally qualifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…Of all identified studies, three main areas were found where they were conducted. The largest group was related to influencing prescribing behavior among physicians [ 42 61 ] ( n = 20), a second group aimed to evaluate ways to stimulate vaccine uptake [ 62 75 ] ( n = 14), and a last group examined methods to increase medication adherence [ 76 85 ] ( n = 10). Identified studies were conducted in the USA ( n = 32) [ 42 , 44 53 , 56 , 58 61 , 64 , 66 , 68 72 , 74 , 75 , 78 84 ], the UK ( n = 6) [ 43 , 54 , 55 , 57 , 63 , 85 ], Singapore ( n = 1) [ 76 ], Tanzania ( n = 1) [ 77 ], Germany ( n = 1) [ 62 ], France ( n = 1) [ 73 ], Australia ( n = 1) [ 67 ], and the Netherlands ( n = 1) [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of all identified studies, three main areas were found where they were conducted. The largest group was related to influencing prescribing behavior among physicians [ 42 61 ] ( n = 20), a second group aimed to evaluate ways to stimulate vaccine uptake [ 62 75 ] ( n = 14), and a last group examined methods to increase medication adherence [ 76 85 ] ( n = 10). Identified studies were conducted in the USA ( n = 32) [ 42 , 44 53 , 56 , 58 61 , 64 , 66 , 68 72 , 74 , 75 , 78 84 ], the UK ( n = 6) [ 43 , 54 , 55 , 57 , 63 , 85 ], Singapore ( n = 1) [ 76 ], Tanzania ( n = 1) [ 77 ], Germany ( n = 1) [ 62 ], France ( n = 1) [ 73 ], Australia ( n = 1) [ 67 ], and the Netherlands ( n = 1) [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Multiple behavioral concepts were tested in the identified studies, but the majority involved social norms [ 44 46 , 48 50 , 54 , 56 , 57 , 59 , 62 64 , 69 , 77 , 81 ] ( n = 16), defaults [ 42 , 43 , 47 , 50 , 51 , 53 , 55 58 , 65 , 68 , 82 ] ( n = 13), availability [ 44 , 45 , 50 , 52 , 60 , 71 , 72 , 75 ] ( n = 8), framing [ 44 , 47 , 56 , 61 ] ( n = 4), loss aversion [ 76 , 79 , 80 ] ( n = 3), and present bias [ 76 , 79 ] ( n = 1). A variety of study designs was observed among all studies, but most were randomized controlled trials [ 44 , 46 , 47 , 49 , 50 , 54 , 59 , 60 , 63 65 , 67 70 , 73 76 , 78 85 ] ( n = 27).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review of 15 studies, evaluating 20 different intervention studies found that 20% of the interventions did not work [ 25 ]. Nudges are designed to non-coercively influence behaviour without forbidding options [ 26 , 27 , 28 , 29 ], and it is the clinicians who must interpret and act. Four potential reasons why our nudges did not change prescribing are explored here.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review of 15 studies, evaluating 20 different interventions studies found that 20% of the intervention did not work [11]. Nudges are designed to non-coercively influence behaviour without forbidding options [12][13][14][15], and it is the clinicians who must interpret and act. If clinicians do not trust the message, delivered in the electronic prescribing system (or its assumed messenger), they may purposely choose to go against it.…”
Section: Discussionmentioning
confidence: 99%